Journal of a contract killer [videorecording (DVD)] - Powell, Justine; Leese, Adam, 1976-; Canuso, Jake; Gambino, Marco; Maylam, Tony; Damiano, Michele (Vanguard, 2010)
Stephanie Komack was a high-class hooker and assassin for the Italian Mob. Now working in London as a waitress and a single mother to her seven year old daughter, the mob tracks Stephanie down and persuades her to do one last job. The hit goes wrong and Stephanie soon realizes the stark consequences of her failure. They snatch her daughter as punishment, but didn't figure on Stephanie's capacity for revenge!